ON THE SPECIFICS OF EDUCATIONAL MATERIALS CORRESPONDING TO MULTILEVEL EDUCATIONAL SYSTEM - Igor N. Kim (Высшее образование в России)
Effective training of bachelors and masters within the framework ofa competency approach is possible only in case of availability of educational materials with a high research and innovative as well as academic potential. Considering that none of the higher educational institutions has enough resources to develop “groundbreaking” educational materials for all directions and areas of personnel training it would be useful to regulate education materials publication in certain educational institutions in order to intensify their exchange and to create writing teams for publishing inter@university series of textbooks and training aids.